Ocular manifestations in adolescent cystinosis: Case report in Thailand - Naris Kitnarong (2018)
Three siblings with a family history of consanguinity presented with short stature and two of the patients had leg deformity. None of them experienced ocular or renal symptoms at presentation. After the pediatricians found characteristics of Fanconi syndrome, an ophthalmic consultation was requested. Ocular examination revealed typical cystine crystals deposited in the cornea and conjunctivae. No crystal deposits were found elsewhere in the eyes. Fundoscopic examination was normal. Two patients who underwent a complete ocular examination were diagnosed as adolescent cystinosis. The youngest patient who lost to follow up before completed ocular examination was suspected for adolescent cystinosis. This is the first report of cystinosis with ocular manifestation from Thailand.